Enhancing Early Childhood Recognition of Traditional Dance through Training Strategies and Video-Based Instruction - Andika Sari, Diah; Anhusadar, Laode; Jovanka, Della Raymena; Magta, Mutiara (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
To introduce traditional dance to early childhood, interesting training methods and media in accordance with the child's development are needed, so as to arouse children's interest and love for traditional Indonesian dance. This study aimed to obtain an empirical data on the effect of training methods and video tutorials on the ability to recognize traditional Indonesian dance in children. Children’s ability to dance traditional dances referred to the motor skills of children aged 5-6 years. The training method was using a sports approach, consists of introduction regional knowledge of dance, a warm-up, traditional dance as the main exercise, and a cool-down. The warm-up and cool-down used play movements, which made children enjoyable and developmentally appropriate. Used experimental research methods 2x2 factorial design, which consists of groups that get treatment and control groups. The sampling technique was carried out by cluster random sampling, 43 children in 2 classes at 2 kindergartens (four classes), in South Tangerang, Indonesia. Data normality test with Lilliefors test found that all data were normal. Homogeneity test with Bartlett's test found that all data were homogeneous. For hypothesis testing, two-way analysis of variance / ANOVA was carried out, then to test the interaction was carried out with the Tukey test. Based on the results of the analysis of variance at a significant level α = 0.05, it was found that the score of the ability to recognize traditional Indonesian dances early childhood: the training method with a sports approach was better than the conventional training method; there was an interaction between training methods; Using video tutorial media was not better than audio media; with a sports approach and video tutorials. This study showed that using a sports-based training approach with play movements is a fun and developmentally appropriate method to introduce traditional dance to children. Further research is needed on a larger and broader scale to conclude that this method has the same effect on every traditional dance practice for early childhood children.